Evaluation of the perceived social impacts of the Formula E Grand Prix of Santiago de Chile - David Parra-Camacho; Daniel Michel Duclos Bastías; Frano Giakoni Ramírez; Samuel López-Carril (European Journal of Government and Economics (EJGE), 2020)
The aim of this study is to analyse residents' perception of the social impact of the Formula E Grand Prix of Santiago de Chile. A sample of 414 residents was collected through a questionnaire made up of 46 items regarding possible positive and negative impacts. Descriptive analysis, confirmatory factorial analysis and cluster analysis were performed. The results showed two groups with different perceptions of this sporting event: realistic (n=152) and favourable (n=162). Sociodemographic variables referring to education level, civil status, income level, location of the family residence and political orientation contribute to significantly differentiating the clusters. The variables related to interest in the event, support for the celebration, attendance, participation and frequency of contact also contributed to significantly differentiating the groups. Citizens' high degree of support for holding the sporting event could be identified by a positive social representation of the event.
Keywords: M14; L8; Z2; 330; clusters; resident's perception; social impact; social representations; sport event